Laboratory and field soil permeability test - Chan, Win Kit (Nanyang Technological University, 2020)
Residual soils are soils weathered in-situ and are found on the surface. Properties of residual soils vary depending on the location and depth of weathering of the soils. The permeability of the soils is one of the soil properties that can be used to investigate the spatial variation of residual soils. The aim of this final year project is to determine the effects of spatial variation on the permeability of surface residual soils. In addition, it also seek to determine the correlation between the field and laboratory permeability tests. Field test was done with the use of tension disk infiltrometers at different test sites at Nanyang Technological University (NTU) located within the Jurong formation. Laboratory tests, which includes the falling-head permeability tests and pressure plate tests, were done on soil samples that were collected from each test. Interpretation of infiltration test data from the disk infiltrometers were done with the use of DISC software which can inversely estimate the hydraulic soil property (saturated permeability, ks and SWCC curve fitting parameters α and n). Comparison of permeability between sites and different test points within the same site showed that spatial variation has significant effect on the permeability of soil. In fact, permeability of soil might even vary within the same test site showing the heterogeneity of residual soils. Infiltration data interpretation by DISC revealed the reliability of the software to estimate the saturated permeability and the van Genuchten SWCC parameters α and n of the soil. However, DISC was found to give a different n compared to the laboratory determined SWCC.